If i am given a linear transformation D:A->A,that is followed by(adsbygoogle = window.adsbygoogle || []).push({});

A=ImD(+)kerD

and i am asked to prove that kerD^2=kerD and imD=imD^2.

instead of trying to work it out the hard way by showing that every element of KerD is an element of kerD^2 , both directions.

would it not be easier to just say that dimA=dimA and hence the two structures are isomorphic which means that KerD={0} and ImD=A.

same goes for D^2:A->A

KerD^2={0}

ImD^2=A

=> therefore KerD^2=KerD and ImD^2=ImD ?

**Physics Forums | Science Articles, Homework Help, Discussion**

Dismiss Notice

Join Physics Forums Today!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Linear transformations

**Physics Forums | Science Articles, Homework Help, Discussion**